2023
DOI: 10.1038/s41598-022-25570-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial integration framework of solar, wind, and hydropower energy potential in Southeast Asia

Abstract: Amid its massive increase in energy demand, Southeast Asia has pledged to increase its use of renewable energy by up to 23% by 2025. Geospatial technology approaches that integrate statistical data, spatial models, earth observation satellite data, and climate modeling can be used to conduct strategic analyses for understanding the potential and efficiency of renewable energy development. This study aims to create the first spatial model of its kind in Southeast Asia to develop multi-renewable energy from sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…While dams may benefit some species through, for instance, the creation of artificial wetlands, protected areas that contain dams cannot be considered to offer protection to the associated ecosystems (Sakti et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While dams may benefit some species through, for instance, the creation of artificial wetlands, protected areas that contain dams cannot be considered to offer protection to the associated ecosystems (Sakti et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This will inevitably entail significant changes in land use to accommodate solar, wind, and hydropower. In their analysis of the potential for energy development in the region, Sakti et al ( 2023 ) found that areas in northern Southeast Asia (Vietnam, Laos, Thailand, and the Philippines) had the highest potential for developing power from all three sources. The intention of Lao PDR to become the “battery of Southeast Asia” has resulted in over 50 hydroelectric dams in 15 years, with a further 101 under construction or planned (Chang, 2013 ; Williams, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second decade of the 21st century has seen renewed interest in hydroelectricity, including both conventional and pumped storage methods, as a clean, renewable, and environmentally friendly source of energy that could contribute to reducing the world’s reliance on burning fossil fuels. , Many proponents of hydropower development have promoted small and “run of the river” hydropower (RORH) as solutions to the problems typically associated with the construction of larger dams and/or reservoirs, as well as climate resilience. Interest has particularly focused on developing economies, where it is believed there is an untapped potential for additional sustainable hydraulic development. …”
Section: Problematic Powermentioning
confidence: 99%